THE CONCEPT OF INVERTED TOTALITARIANISM IN POLITICAL PHILOSOPHY OF SHELDON WOLIN - Valantiejus, Vaidotas (Sociologija. Mintis ir veiksmas, 2016)
The main task of this article is to analyze the relationship between totalitarianism and democracy in relation with the concept of inverted totalitarianism by Sheldon S. Wolin. The article argues that the possibilities of inverted totalitarianism are inherent within democracy itself. The tendencies of inverted totalitarianism are not only the trait of concrete political regime, but also intrinsic to global political and economic structure. The article asserts that the disciplinary tendencies in contemporary societies are radically changing the classical idea of „rule by the people“. The main conclusion is that we are witnessing not only the inversions of totalitarianism, but also the inversions of democracy. This new form of democracy can be called a total democracy without demos.
Keywords: inverted totalitarianism; managed democracy; political; empire